PENGARUH PROFITABILITAS (NPM) DAN UKURAN PERUSAHAAN (FIRM SIZE) TERHADAP HARGA SAHAM (CLOSING PRICE) PT MITRA ADI PERKASA TAHUN 2014-2023 - Karla Anggita Mutiarani; Nurismalatri (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of Profitability (NPM), as measured by profitability (NPM), and firm size on the stock price (closing price) of PT Mitra Adi Perkasa during the period 2014-2023. The research method used is a quantitative method with secondary data in the form of annual financial reports published during that period. This study uses descriptive statistical analysis, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination as data analysis methods. The results of this study indicate that partially Profitability (NPM) shows that the t-value is -1286 <1.894 with a significance value obtained of 0.239> 0.05, then Ho is accepted and Ha is rejected, meaning that Profitability (NPM) has no effect on the stock price (closing price) at PT Mitra Adi Perkasa. On the variable of company size (firm size) on Stock Price (Closing Price) shows that the calculated t value is 0.942 <1.894 with the significance value obtained is 0.377> 0.05 then Ho is rejected and Ha is accepted the company size (firm size) has no effect on the stock price (closing price) at PT. Mitra Adi Perkasa. Simultaneously the calculated F value is 0.834 <5.59 and the significance value is 0.473> 0.05 then together, profitability (NPM) and company size (firm size) have no effect on the stock price (closing price) of PT. Mitra Adiperkasa. Based on the results of the coefficient of determination test of the Profitability (NPM) and company size variables, the value obtained is 0.193 giving a significant impact of 19.3% on the stock price (closing price), while the remaining 80.7% is influenced by factors that have not been studied. The results of this study indicate that Profitability (NPM) and Firm Size do not affect stock prices (closing prices).